Collaborative board games a tool in developing social interest among 7 years old children - Tayag, Stephany S.; Reynoso, Johnny T. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Young people play an important role in nation building since they will be the one who will take responsibility over the country as generations pass. The way the youth perceive society can make or break the future of the nation. With the youth's strong idealism, they can have the power to break the hegemonies and the injustices the country might face. Aside from believing in the power of young people, Rizal also hoped for a society where the people from an ethical community, working together for a common good that will benefit the whole nation.

However, studies have shown that the Filipino youth are growing up in a damaged culture - a culture where they don't prioritize the welfare of the nation, instead, they only focus on smaller units of society that are closer to them: family, friends, relationships, etc.

The study focuses on diagnosing social apathy among 7 years old children and treating them using the use of collaborative board games. The results showed that the children are somehow apathetic to the concerns of other children, but after playing the game, they have learned the basics of cooperation, unity, and empathy, the basic elements of social interest.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 29-31
Keywords: Board games; Empathy -- Youth; Social interest -- Youth; Children and society; Youth